Análise da autoeficácia e perfeccionismo em árbitros de natação do Brasil - Guilherme Moraes Balbim; Regina Alves Thon; Renato Melo Ferreira; Lenamar Fiorese Vieira (Universidade Estadual do Oeste do Paraná, 2015)
The study aimed to analyze perfectionism and self-efficacy levels in swimming's referees from Brazil. The sample was composed by 150 referees, 72 male and 78 female, with at least one year of experience in official federation's staff, 34 from state level, 66 national and 50 international. As instruments was utilized: identification form, General Perceived Self-efficacy Scale and Multidimensional Perfectionism Scale. Data were collected during competitions of official calendar from Brazilian Confederation of Aquatic Sports in 2011 and 2012. In statistical analysis were utilized the tests: Kolmogorov-Smirnov, Mann-Whitney, Kruskall-Wallis, Friedman and Spearman correlation coefficient, with p<0,05. It was observed that organization was the perfectionism characteristic that obtained the highest score, female referees showed higher levels of concern over mistakes, doubts about actions and negative perfectionism than male referees, besides, state-level referees showed higher levels of parental expectations, personal standards and positive perfectionism than national-level. It was concluded that swimming referees showed high levels of self-efficacy and organization; female referees had higher scores in concern over mistakes, doubts about actions and negative perfectionism; there is no correlation between self-efficacy and perfectionism in Brazilian swimming referees.